1976
DOI: 10.1080/00207597608247349
|View full text |Cite
|
Sign up to set email alerts
|

Differential cognitive cues in pictorial depth perception among Ugandan children

Abstract: Four pictures from Hudson's Depth Perception Test containing size, superposition or overlap, and linear perspective cues were administered to 240 Ugandan primary school children. The key question asked regarding the relationship of elements in each picture varied in terms of "Which (isilooks) (nearerlfarther) to (man/you), the elephant or the antelope ?". Results suggested that depth in pictorial material was perceived significantly higher for the question variation "which is/looks farther" rather than "neare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…African children demonstrated great difficulty in perceiving depth in these pictures. This finding was replicated with children in several other African countries (Deregowski, ; Mundy‐Castle, ; Omari & MacGinitie, ; Opolot, ). These authors all concluded that the ability to perceive pictures in three dimensions depends heavily on experience with pictorial materials.…”
Section: Cross‐cultural Issues In Child Assessmentsupporting
confidence: 55%
“…African children demonstrated great difficulty in perceiving depth in these pictures. This finding was replicated with children in several other African countries (Deregowski, ; Mundy‐Castle, ; Omari & MacGinitie, ; Opolot, ). These authors all concluded that the ability to perceive pictures in three dimensions depends heavily on experience with pictorial materials.…”
Section: Cross‐cultural Issues In Child Assessmentsupporting
confidence: 55%